THE INFLUENCE OF SOCIAL MEDIA MARKETING AND ELECTRONIC WORDS OF MOUTH ON INTEREST IN BUYING SNEAKMARKET PRODUCTS WITH BRAND IMAGE AS INTERVENING VARIABLE - Irzaki, M. Alfin; Taufiqurrahman, Taufiqurrahman; Musfar, Tengku Firli (International Journal of Economic, Business & Applications, 2024)
This research, which aims to determine and analyze the influence of social media marketing and electronic word of mouth on interest in buying Sneakmarket products, with brand image as an intervening variable, was conducted using a rigorous methodology. The research method used is descriptive, involving 120 followers on the Sneakmarket Instagram account in Pekanbaru City. The sampling method was non-probabilistic, ensuring a diverse range of respondents. Respondent data was processed using the SmartPLS version 4 analysis technique, a widely accepted method in the field. The research showed that social media marketing, electronic word of mouth, and brand image positively affected interest in purchasing Sneakmarket products directly and indirectly, providing valuable insights.